Thermal-insulation cement mortar board capable of degrading nitric oxide gas as well as preparation method and application of thermal-insulation cement mortar board

By using polylactic acid modified hollow titanium dioxide microspheres and foaming agent in cement mortar boards, the porosity and mechanical properties of cement mortar boards are improved, and the problem that existing cement materials cannot effectively degrade nitrogen oxides is solved, achieving high efficiency Degrading nitric oxide and good insulation performance meet the requirements of building energy conservation and environmental protection.

CN119430798APending Publication Date: 2025-02-14BEIJING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411584349.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing cement materials have a single function, cannot effectively degrade nitrogen oxides in the air, cannot achieve the effect of purifying the air, and cannot meet the requirements of building energy conservation and environmental protection.

Method used

Polylactic acid modified hollow titanium dioxide microspheres are used as functional materials, combined with a specific content of foaming agent to improve the porosity and mechanical properties of cement mortar boards, and significantly improve its degradation ability and insulation function of nitric oxide gas.

Benefits of technology

The cement mortar board has achieved efficient degradation of nitric oxide, with a degradation rate of up to 16ppb/h/m2 or above, a thermal conductivity of 0.04~0.06W/(m·K), and a compressive strength of up to 0.7MPa or above, satisfying the construction materials. the insulation needs while improving air quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430798A_ABST
    Figure CN119430798A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and particularly discloses a thermal insulation cement mortar plate capable of degrading nitric oxide gas as well as a preparation method and application of the thermal insulation cement mortar plate. The cement mortar board comprises the following components: 19%-23% of cement, 61%-67% of standard sand, 3.2%-4.6% of polylactic acid modified hollow titanium dioxide microspheres, 0.05%-0.1% of a water reducing agent, 0.02%-0.04% of a foaming agent and 9%-12% of water. The polylactic acid modified hollow titanium dioxide is added to serve as a functional material, meanwhile, the foaming agent is added to regulate and control the porosity in the cement mortar board, the cement mortar board with the dual functions of heat preservation and photocatalytic degradation of nitric oxide is formed, meanwhile, polylactic acid is a biodegradable material, and the thermal insulation effect is good. The invention provides an energy-saving and environment-friendly green multifunctional material for the building field, is suitable for various building structures and application scenes, and has high practical value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a thermal insulation cement mortar board capable of degrading nitric oxide gas, and a preparation method and application thereof. Background Art

[0002] With the continuous deepening of industrialization and urbanization and the continuous improvement of economic level, the combustion of coal and oil, industrial waste gas and automobile exhaust emissions have produced a large amount of harmful gases such as nitrogen oxides and sulfur oxides. These gases are the main components of air pollution and will cause a significant decline in air quality. Excessive emissions of nitrogen oxides will not only harm the human body and respiratory tract, but also participate in the formation of photochemical smog, ozone, haze, etc. Therefore, how to deal with nitrogen oxide harmful gases in a timely manner and reduce their impact on the human body and the environment has become an urgent problem to be solved.

[0003] Cement materials are one of the most widely used building materials in the world, with an annual cement production of more than 2 billion tons nationwide. Cement-based materials are multiphase porous materials whose pore sizes can range from nanometers to millimeters. The wide range of pore distribution determines that cement-based materials have high adsorption properties. Therefore, they are expected to be used in photocatalytic oxidation and adsorption of nitrogen oxides in the air. However, the current cement-based materials have a single function and poor degradation effect on nitrogen oxides, and cannot achieve the effect of effectively purifying the air. With the intensification of the global energy crisis and environmental pollution, building energy conservation and environmental protection have become the focus of global attention. Therefore, it is necessary to provide a multifunctional cement material that can effectively degrade nitrogen oxides in the air to meet the requirements of today's society for building energy conservation and environmental protection. Summary of the invention

[0004] In view of the problem that cement materials in the prior art have a single function and cannot meet the requirements of today's society for energy-saving and environmentally friendly building materials, the present invention provides a thermal insulation cement mortar board capable of degrading nitric oxide gas, and a preparation method and application thereof.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0006] A thermal insulation cement mortar board capable of degrading nitric oxide gas comprises the following raw material components in percentage by mass: 19% to 23% cement, 61% to 67% standard sand, 3.2% to 4.6% polylactic acid modified hollow titanium dioxide microspheres, 0.05% to 0.1% water reducing agent, 0.02% to 0.04% foaming agent and 9% to 12% water.

[0007] Compared with the prior art, the cement mortar board provided by the present invention uses polylactic acid modified hollow titanium dioxide microspheres as functional materials. The addition of polylactic acid modified hollow titanium dioxide microspheres can significantly improve the degradation ability of the cement mortar board to nitric oxide gas and the thermal insulation function. At the same time, the addition of polylactic acid modified hollow titanium dioxide microspheres can also improve the mechanical properties of the cement mortar board. In addition, the addition of a specific content of foaming agent can increase the porosity inside the cement mortar board while ensuring the mechanical properties of the cement mortar board, thereby improving its adsorption capacity for nitric oxide, which is beneficial for the polylactic acid modified hollow titanium dioxide microspheres to fully degrade nitric oxide and improve the ability of the cement mortar board to purify the air.

[0008] The thermal insulation cement mortar board provided by the present invention can achieve a degradation rate of nitric oxide of up to 16ppb / h / m 2 The above, thermal conductivity is 0.04 ~ 0.06W / (m K), compressive strength can reach more than 0.7MPa, can be widely used in building materials insulation, can not only effectively reduce the energy consumption of buildings, but also to a certain extent to improve the air quality, in line with the current society's requirements for green energy-saving and environmental protection of building materials, with high economic and environmental benefits.

[0009] Furthermore, the cement is PO32.5 or PO42.5 ordinary Portland cement, wherein the mass percentage of dicalcium silicate is 25% to 35%, and the mass percentage of tricalcium silicate is 55% to 75%.

[0010] Furthermore, the particle size of the standard sand is 1.18 mm to 2.36 mm, and the content of silicon dioxide is not less than 98%.

[0011] Furthermore, the average particle size of the polylactic acid modified hollow titanium dioxide microspheres is 200nm to 240nm, and the specific surface area is 50m 2 / g~60m 2 / g.

[0012] Polylactic acid-modified hollow titanium dioxide combines the biodegradability of polylactic acid and the photocatalytic property of titanium dioxide, and can provide a new functional material for cement materials that is both environmentally friendly and has air purification function. At the same time, the degradation ability of hollow titanium dioxide modified by polylactic acid is significantly improved for nitric oxide, and through the synergistic effect of polylactic acid and titanium dioxide, the thermal insulation and mechanical properties of cement mortar board are also significantly improved.

[0013] Furthermore, the preparation method of the polylactic acid modified hollow silica microspheres comprises the following steps:

[0014] Add monodisperse polylactic acid microsphere emulsion and ammonia water into anhydrous ethanol, mix evenly, add a mixed solution of tetrabutyl titanate, triethanolamine and anhydrous ethanol, react at 70°C to 90°C for 7h to 9h, separate the solid and liquid, dry, and calcine the dried product at 280°C to 300°C for 10h to 14h to obtain polylactic acid modified hollow titanium dioxide microspheres.

[0015] Specifically, the mass ratio of the monodisperse polylactic acid microsphere emulsion, ammonia water, tetrabutyl titanate and triethanolamine is 13-16:70-80:15-20:1-2.

[0016] Specifically, the preparation method of the polylactic acid modified hollow silica microspheres comprises the following steps:

[0017] Add 13-16 parts of monodisperse polylactic acid microsphere emulsion and 70-80 parts of ammonia water to 100 parts of anhydrous ethanol, mix well, transfer to a three-necked flask with a stirrer, add a mixed solution of 15-20 parts of tetrabutyl titanate, 1-2 parts of triethanolamine and 20 parts of anhydrous ethanol, and slowly dropwise add at a uniform speed for 1.5-2 hours. After the addition is completed, heat to 70°C-90°C and react for 7h-9h, centrifuge, wash, and dry. Calcine the dried product at 280°C-300°C for 10h-14h, cool to room temperature, and obtain polylactic acid modified hollow titanium dioxide microspheres.

[0018] Furthermore, the water reducing agent is a polycarboxylic acid-based water reducing agent.

[0019] Furthermore, the foaming agent is sodium lauryl sulfate.

[0020] The present invention also provides a method for preparing the above-mentioned thermal insulation cement mortar board capable of degrading nitric oxide gas, comprising the following steps:

[0021] Step 1: weigh each component according to the designed ratio, dilute the weighed foaming agent with water by 20 to 40 times to obtain foam;

[0022] The weighed polylactic acid modified hollow titanium dioxide microspheres, water reducing agent and remaining water are dispersed uniformly, and then cement and standard sand are added in sequence to obtain a primary mixture;

[0023] Step 2, adding the foam into the primary mixture, mixing evenly, to obtain cement mortar;

[0024] Step three: pouring the cement mortar into a mold, removing the mold after the mortar is solidified, and performing curing to obtain a thermal insulation cement mortar board capable of degrading nitric oxide gas.

[0025] The preparation method of the thermal insulation cement mortar board capable of degrading nitric oxide gas provided by the present invention is simple to operate, can be produced continuously, greatly reduces the production cost, and is easy to realize industrialized production.

[0026] The present invention also provides application of the thermal insulation cement mortar board capable of degrading nitric oxide gas in building materials.

[0027] The thermal insulation cement mortar board provided by the present invention adds polylactic acid modified hollow titanium dioxide as a functional material. At the same time, a foaming agent is added to adjust the porosity in the cement mortar board, thereby forming a cement mortar board with the dual functions of thermal insulation and photocatalytic degradation of nitric oxide. At the same time, polylactic acid is a biodegradable material, which provides an energy-saving and environmentally friendly green multifunctional material for the construction field, is suitable for various building structures and application scenarios, and has high practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a SEM image of the polylactic acid modified hollow titanium dioxide prepared in Example 1 of the present invention;

[0029] Figure 2 It is a schematic diagram of testing the compressive strength of the cement mortar board of the present invention;

[0030] Figure 3 This is a schematic diagram of testing the efficiency of photocatalytic degradation of nitric oxide by the cement mortar board of the present invention;

[0031] Figure 4 It is a schematic diagram of testing the thermal conductivity of the cement mortar board of the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] The monodisperse polylactic acid microsphere emulsion used in the following examples and comparative examples was purchased from Zhongke Keyou. The cement used was PO42.5. The particle size of the standard sand was 1.18 mm to 2.36 mm, and the content of silicon dioxide was not less than 98%. The solid content of the polycarboxylate water reducer was 30%, and the water reduction rate was 35%.

[0034] Example 1

[0035] This embodiment provides a method for preparing polylactic acid modified hollow titanium dioxide, comprising the following steps:

[0036] Add 15 parts of monodisperse polylactic acid microsphere emulsion and 75 parts of ammonia water into 100 parts of anhydrous ethanol, mix well, transfer to a three-necked flask with a stirrer, add a mixed solution of 15 parts of tetrabutyl titanate, 1 part of triethanolamine and 20 parts of anhydrous ethanol, and slowly dropwise add at a uniform speed for 2 hours. After the addition is completed, heat to 80°C and react for 8 hours, centrifuge, wash, and dry. Calcine the dried product at 290°C for 12 hours, cool to room temperature, and obtain polylactic acid modified hollow titanium dioxide microspheres.

[0037] The average particle size of the prepared polylactic acid modified hollow titanium dioxide microspheres is 200nm-240nm, and the specific surface area is 50m 2 / g~60m 2 / g.

[0038] The SEM image of the polylactic acid modified hollow titanium dioxide microspheres prepared in this example is as follows: Figure 1 As shown in the figure, it can be seen that it is a porous hollow structure microsphere.

[0039] By replacing the reaction conditions of Example 1 with other reaction conditions specified in the present invention, such as replacing the mass of the reaction raw materials, the reaction temperature, the calcination temperature and time with other conditions specified in the present invention, the technical effect equivalent to that of the polylactic acid modified hollow titanium dioxide microspheres prepared in Example 1 can be achieved.

[0040] Example 2

[0041] This embodiment provides a thermal insulation cement mortar board capable of degrading nitric oxide gas, comprising the following raw material components in percentage by weight:

[0042] Cement 21.2%, standard sand 63.6%, polylactic acid modified hollow titanium dioxide microspheres 4.53%, polycarboxylate water reducer 0.05%, sodium lauryl sulfate 0.02% and water 10.6%.

[0043] The preparation method of the thermal insulation cement mortar board capable of degrading nitric oxide gas comprises the following steps:

[0044] Weigh each component according to the designed ratio, dilute the weighed sodium dodecyl sulfate with water 20-40 times to obtain foam;

[0045] The weighed polylactic acid-modified hollow titanium dioxide, polycarboxylate water-reducing agent and water were added to an ultrasonic cell disruptor for ultrasonic dispersion at a power of 650 W and a dispersion time of 25 min, and then added to a cement mortar mixer, stirred at a rate of 62 r / min for 60 s, and then stirred at a rate of 125 r / min for 60 s, and then the above foam was added, stirred at a rate of 62 r / min for 60 s and then stirred at a rate of 125 r / min for 60 s to obtain cement mortar;

[0046] Pour cement mortar into the board mold, remove the mold after the mortar slurry solidifies, put it into a curing box with a temperature of 20±2°C and a humidity of >95% for curing for 28 days, and obtain a thermal insulation cement mortar board that can degrade nitric oxide gas.

[0047] Example 3

[0048] This embodiment provides a thermal insulation cement mortar board capable of degrading nitric oxide gas, comprising the following raw material components in percentage by weight:

[0049] Cement 23%, standard sand 61.7%, polylactic acid modified hollow titanium dioxide microspheres 3.2%, polycarboxylate water reducer 0.08%, sodium lauryl sulfate 0.02% and water 12%.

[0050] The preparation method of the thermal insulation cement mortar board capable of degrading nitric oxide gas comprises the following steps:

[0051] Weigh each component according to the designed ratio, dilute the weighed sodium dodecyl sulfate with water 20-40 times to obtain foam;

[0052] The weighed polylactic acid-modified hollow titanium dioxide, polycarboxylate water-reducing agent and water were added to an ultrasonic cell disruptor for ultrasonic dispersion at a power of 650 W and a dispersion time of 20 min, and then added to a cement mortar mixer, stirred at a rate of 62 r / min for 60 s, and then stirred at a rate of 125 r / min for 60 s, and then the above foam was added, and stirred at a rate of 62 r / min for 60 s and then stirred at a rate of 125 r / min for 60 s to obtain cement mortar;

[0053] Pour cement mortar into the board mold, remove the mold after the mortar slurry solidifies, put it into a curing box with a temperature of 20±2°C and a humidity of >95% for curing for 28 days, and obtain a thermal insulation cement mortar board that can degrade nitric oxide gas.

[0054] Example 4

[0055] This embodiment provides a thermal insulation cement mortar board capable of degrading nitric oxide gas, comprising the following raw material components in percentage by weight:

[0056] Cement 19%, standard sand 67%, polylactic acid modified hollow titanium dioxide microspheres 4.6%, polycarboxylate water reducer 0.1%, sodium lauryl sulfate 0.04% and water 9.26%.

[0057] The preparation method of the thermal insulation cement mortar board capable of degrading nitric oxide gas comprises the following steps:

[0058] Weigh each component according to the designed ratio, dilute the weighed sodium dodecyl sulfate with water 20-40 times to obtain foam;

[0059] The weighed polylactic acid-modified hollow titanium dioxide, polycarboxylate water-reducing agent and water were added to an ultrasonic cell disruptor for ultrasonic dispersion at a power of 650 W and a dispersion time of 30 min, and then added to a cement mortar mixer, stirred at a rate of 62 r / min for 60 s, and then stirred at a rate of 125 r / min for 60 s, and then the above foam was added, and stirred at a rate of 62 r / min for 60 s and then stirred at a rate of 125 r / min for 60 s to obtain cement mortar;

[0060] Pour cement mortar into the board mold, remove the mold after the mortar slurry solidifies, put it into a curing box with a temperature of 20±2°C and a humidity of >95% for curing for 28 days, and obtain a thermal insulation cement mortar board that can degrade nitric oxide gas.

[0061] Comparative Example 1

[0062] This comparative example provides a thermal insulation cement mortar board capable of degrading nitric oxide gas, which is different from Example 2 only in that polylactic acid-modified hollow titanium dioxide microspheres are not added. The specific ingredients are as follows:

[0063] Cement 22.67%, standard sand 65.7%, polycarboxylate water reducer 0.38%, sodium lauryl sulfate 0.02% and water 11.23%.

[0064] The preparation method of the thermal insulation cement mortar board capable of degrading nitric oxide gas comprises the following steps:

[0065] Weigh each component according to the designed ratio, add the weighed polycarboxylate water-reducing agent and water into an ultrasonic cell disruptor for ultrasonic dispersion at a power of 650 W and a dispersion time of 25 min, then add into a cement mortar mixer, stir at a rate of 62 r / min for 60 s, add weighed standard sand, stir at a rate of 62 r / min for 60 s, and then stir at a rate of 125 r / min for 60 s to obtain cement mortar;

[0066] Pour cement mortar into the board mold, remove the mold after the mortar slurry solidifies, put it into a curing box with a temperature of 20±2°C and a humidity of >95% for curing for 28 days, and obtain a thermal insulation cement mortar board that can degrade nitric oxide gas.

[0067] Comparative Example 2

[0068] This comparative example provides a thermal insulation cement mortar board capable of degrading nitric oxide gas, which is different from Example 2 only in that ordinary nano titanium dioxide microspheres (average particle size of 320 nm, specific surface area of ​​100 m 2 / g), the specific ingredients are as follows:

[0069] Cement 21.2%, standard sand 63.6%, nano titanium dioxide microspheres 4.53%, polycarboxylate water reducer 0.05%, sodium lauryl sulfate 0.02% and water 10.6%.

[0070] The preparation method of the thermal insulation cement mortar board capable of degrading nitric oxide gas comprises the following steps:

[0071] Weigh each component according to the designed ratio, dilute the weighed sodium dodecyl sulfate with water 20-40 times to obtain foam;

[0072] The weighed nano-titanium dioxide microspheres, polycarboxylate water-reducing agent and water were added to an ultrasonic cell disruptor for ultrasonic dispersion at a power of 650 W and a dispersion time of 25 min, and then added to a cement mortar mixer, stirred at a rate of 62 r / min for 60 s, and then stirred at a rate of 125 r / min for 60 s, and then the above foam was added, stirred at a rate of 62 r / min for 60 s and then stirred at a rate of 125 r / min for 60 s, to obtain cement mortar;

[0073] Pour cement mortar into the board mold, remove the mold after the mortar slurry solidifies, put it into a curing box with a temperature of 20±2°C and a humidity of >95% for curing for 28 days, and obtain a thermal insulation cement mortar board that can degrade nitric oxide gas.

[0074] Comparative Example 3

[0075] This comparative example provides a thermal insulation cement mortar board capable of degrading nitric oxide gas. The only difference from Example 2 is that the polylactic acid-modified hollow titanium dioxide is replaced with polystyrene-modified titanium dioxide. The specific ingredients are as follows:

[0076] Cement 21.2%, standard sand 63.6%, polystyrene modified titanium dioxide microspheres 4.53%, polycarboxylate water reducer 0.05%, sodium lauryl sulfate 0.02% and water 10.6%.

[0077] The preparation method of the polystyrene modified titanium dioxide microspheres comprises the following steps:

[0078] Add 15 parts of polystyrene and 75 parts of ammonia water to 100 parts of anhydrous ethanol, mix well, transfer to a three-necked flask with a stirrer, add a mixed solution of 15 parts of tetrabutyl titanate, 1 part of triethanolamine and 20 parts of anhydrous ethanol, and slowly dropwise add at a uniform speed for 2 hours. After the addition is completed, heat to 80°C and react for 8 hours, centrifuge, wash, and dry. Calcine the dried product at 290°C for 12 hours, cool to room temperature, and obtain polystyrene modified titanium dioxide microspheres.

[0079] The preparation method of the thermal insulation cement mortar board capable of degrading nitric oxide gas comprises the following steps:

[0080] Weigh each component according to the designed ratio, dilute the weighed sodium dodecyl sulfate with water 20-40 times to obtain foam;

[0081] The weighed polystyrene modified titanium dioxide, polycarboxylate water reducer and water were added to an ultrasonic cell disruptor for ultrasonic dispersion at a power of 650 W for a dispersion time of 25 min, and then added to a cement mortar mixer, stirred at a rate of 62 r / min for 60 s, and then stirred at a rate of 125 r / min for 60 s, and then the above foam was added, stirred at a rate of 62 r / min for 60 s and then stirred at a rate of 125 r / min for 60 s to obtain cement mortar;

[0082] Pour cement mortar into the board mold, remove the mold after the mortar slurry solidifies, put it into a curing box with a temperature of 20±2°C and a humidity of >95% for curing for 28 days, and obtain a thermal insulation cement mortar board that can degrade nitric oxide gas.

[0083] Performance Testing

[0084] 1. Compressive strength

[0085] The compressive strength test of cement mortar board is determined according to GBT 5486-2008 "Test methods for inorganic rigid insulation products". The specific test process is as follows:

[0086] The size of the specimen used for compressive strength test is 100mm*100mm*25mm, and three specimens are tested in each group of embodiments. Place the specimen on the pressure plate of the testing machine so that the center of the pressure plate of the testing machine coincides with the center of the specimen. Load the specimen at a speed of (10±1)mm / min until the specimen is destroyed, and record the compression deformation value at the same time. If the specimen is not destroyed at a compression deformation of 5%, the load at which the specimen is compressed and deformed by 5% is the destruction load. Record the destruction load P, accurate to 10N. The compressive strength of each specimen is calculated according to the formula Calculation, where P is the failure load, unit N; σ is the compressive strength, unit MPa; S is the compressive area, unit mm 2 The compressive strength result is accurate to 0.01MPa. The compressive strength test diagram is as follows Figure 2 The compressive strength values ​​of all embodiments and comparative examples are shown in Table 1.

[0087] Table 1 Compressive strength of cement mortar board

[0088] Group Compressive strength(MPa) Example 1 0.78 Example 2 0.72 Example 3 0.81 Comparative Example 1 0.53 Comparative Example 2 0.58 Comparative Example 3 0.67

[0089] By comparing Example 1 and Comparative Examples 1-3, it can be seen that the addition of polylactic acid modified hollow titanium dioxide can improve the compressive strength of the cement mortar board. Compared with polystyrene modified titanium dioxide, the improvement of the compressive strength is more obvious.

[0090] 2. Photocatalytic degradation of nitric oxide

[0091] The photocatalytic degradation efficiency of nitric oxide of the cement mortar boards prepared in the examples and comparative examples was tested using a nitrogen oxide analyzer. The instrument was equipped with an 8W ultraviolet lamp, a photocatalytic polymerization glass reactor with a size of 30cm×15cm×10cm, and a humidification chamber, and the nitrogen oxide concentration test range was 0 to 1000ppb.

[0092] The specific test process is: place each group of 3 100mm*100mm*25mm test specimens in the reaction chamber of the nitrogen oxide analyzer, and place an 8W ultraviolet lamp directly above the reactor; then slowly introduce the gas, the airflow is completely premixed by the gas mixer, the flow rates of nitrogen and nitric oxide are controlled by mass flow controllers at 2.4L / min and 24mL / min, respectively, the nitric oxide gas is diluted to about 800ppb by the airflow, and the required relative humidity level of nitric oxide gas is controlled at 50% by passing the airflow through a humidifying chamber. After reaching the adsorption-desorption equilibrium, turn on the ultraviolet lamp to react for 30 minutes. The photocatalytic degradation of nitric oxide by the specimen under ultraviolet light can be obtained by continuously measuring the concentration of nitric oxide by the nitrogen oxide analyzer. Schematic diagram of the photocatalytic degradation of nitric oxide test of cement mortar board is shown in the figure. Figure 3 The photocatalytic degradation efficiency of nitric oxide of all embodiments and comparative examples is shown in Table 2.

[0093] Table 2 Efficiency of cement mortar board in degrading nitric oxide

[0094] Group <![CDATA[Nitric oxide degradation rate (ppb / h / m 2 )]]> Example 1 22.5 Example 2 16.4 Example 3 25.8 Comparative Example 1 5.5 Comparative Example 2 12.8 Comparative Example 3 14.1

[0095] The results show that compared with ordinary titanium dioxide microspheres, polylactic acid modified hollow titanium dioxide has a higher catalytic degradation efficiency for nitric oxide, and is better than polystyrene modified titanium dioxide.

[0096] 3. Thermal conductivity

[0097] The thermal conductivity of cement mortar board is determined according to GB / T10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Guarded Hot Plate Method", and the specific operation is as follows:

[0098] The size of the test piece for thermal conductivity test is 100mm*100mm*25mm, and three test pieces are tested in each group of examples. Place the cement mortar board on the heating plate of the thermal conductivity tester, and then turn the handle so that the test piece is pressed by the cold plate. Note that the contact surface should be kept flat and tightly combined, and the water pipe should be turned on for water cooling. The schematic diagram of thermal conductivity test is shown in the figure below. Figure 4 The thermal conductivity of all embodiments and comparative examples is shown in Table 3.

[0099] Table 3 Thermal conductivity of cement mortar board

[0100]

[0101]

[0102] In summary, the present invention prepares a hollow titanium dioxide microsphere by modifying polylactic acid, and mixes it into cement mortar board, so that the prepared cement mortar board can not only meet the mechanical performance requirements of cement mortar insulation board, but also has high efficiency in degrading nitric oxide gas and good thermal insulation performance. The present invention enriches the function of cement materials, can be better used in the field of construction engineering, and has good application prospects.

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A thermal insulation cement mortar board capable of degrading nitric oxide gas, characterized in that: The invention comprises the following raw material components in percentage by weight: 19% to 23% cement, 61% to 67% standard sand, 3.2% to 4.6% polylactic acid modified hollow titanium dioxide microspheres, 0.05% to 0.1% water reducing agent, 0.02% to 0.04% foaming agent and 9% to 12% water.

2. The thermal insulation cement mortar board capable of degrading nitric oxide gas according to claim 1, characterized in that: The cement is PO32.5 or PO42.5 ordinary Portland cement, wherein the mass percentage of dicalcium silicate is 25% to 35%, and the mass percentage of tricalcium silicate is 55% to 75%.

3. The thermal insulation cement mortar board capable of degrading nitric oxide gas according to claim 1, characterized in that: The particle size of the standard sand is 1.18 mm to 2.36 mm, and the content of silicon dioxide is not less than 98%.

4. The thermal insulation cement mortar board capable of degrading nitric oxide gas according to claim 1, characterized in that: The average particle size of the polylactic acid modified hollow titanium dioxide microspheres is 200nm to 240nm, and the specific surface area is 50m 2 / g~60m 2 / g.

5. The thermal insulation cement mortar board capable of degrading nitric oxide gas according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent.

6. The thermal insulation cement mortar board capable of degrading nitric oxide gas according to claim 1, characterized in that: The foaming agent is sodium lauryl sulfate.

7. The thermal insulation cement mortar board capable of degrading nitric oxide gas according to claim 1 or 4, characterized in that: The preparation method of the polylactic acid modified hollow silica microspheres comprises the following steps: Add monodisperse polylactic acid microsphere emulsion and ammonia water into anhydrous ethanol, mix evenly, add a mixed solution of tetrabutyl titanate, triethanolamine and anhydrous ethanol, react at 70°C to 90°C for 7h to 9h, separate the solid and liquid, dry, and calcine the dried product at 280°C to 300°C for 10h to 14h to obtain polylactic acid modified hollow titanium dioxide microspheres.

8. The thermal insulation cement mortar board capable of degrading nitric oxide gas according to claim 7, characterized in that: The mass ratio of the monodisperse polylactic acid microsphere emulsion, ammonia water, tetrabutyl titanate and triethanolamine is 13-16:70-80:15-20:1-2.

9. The method for preparing the thermal insulation cement mortar board capable of degrading nitric oxide gas according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: weigh each component according to the designed ratio, dilute the weighed foaming agent with water by 20 to 40 times to obtain foam; The weighed polylactic acid modified hollow titanium dioxide microspheres, water reducing agent and remaining water are dispersed uniformly, and then cement and standard sand are added in sequence to obtain a primary mixture; Step 2, adding the foam into the primary mixture, mixing evenly, to obtain cement mortar; Step three: pouring the cement mortar into a mold, removing the mold after the mortar is solidified, and performing curing to obtain a thermal insulation cement mortar board capable of degrading nitric oxide gas.

10. Use of the thermal insulation cement mortar board capable of degrading nitric oxide gas according to any one of claims 1 to 8 in building materials.